Donor efforts to support public sector reform and the 'Second Orthodoxy' in Mozambique and Uganda - Pinnington, LR (2022)
Responding to the failures of the ‘good governance’ agenda in the post-Cold War period, development scholars and practitioners have been advancing approaches that might better contribute to establishing stronger institutions in Africa. Sometimes referred to as the ‘second orthodoxy’ in donor practice, these models aim to take the politics of African contexts seriously and adapt to the realities of the institutional contexts in which they are applied. Despite widespread acceptance of the need for more ‘politically sensitive’ development practice, there remain questions about how such models work in practice and whether they lead to more effective development programming. For instance, by forwarding an approach that works ‘with the grain’ of prevailing political economies, do such models risk simply reinforcing the status quo in terms of how power and resources are distributed? This thesis examines the application of ‘second orthodoxy’ methods in efforts to support public sector reform in two UKAid-funded development programmes. The first is a public financial management technical assistance programme in Uganda: the Budget Strengthening Initiative (BSI). The second is an economic empowerment programme for young urban women in Mozambique (MUVA); the research focuses on its efforts to promote the adoption of gender policy in the education and social protection sectors. Through qualitative within-case analysis, the research seeks to gain a clearer picture of how the ‘second orthodoxy’ is being applied in practice, and both the intended and unintended effects it produces in aid programmes.